A study on the association between infectious burden and Alzheimer's disease. (9th June 2014) - Bu, X.‐L.; Yao, X.‐Q.; Jiao, S.‐S.; Zeng, F.; Liu, Y.‐H.; Xiang, Y.; Liang, C.‐R.; Wang, Q.‐H.; Wang, X.; Cao, H.‐Y.; Yi, X.; Deng, B.; et al.
Abstract : Background and purpose: Previous studies suggested that the overall burden of prior infections contributes to cardiovascular diseases and stroke. In the present study, the association between infectious burden (IB) and Alzheimer's disease (AD) was examined. Methods: Antibody titers to common infectious pathogens including cytomegalovirus (CMV), herpes simplex virus type 1 (HSV‐1), Borrelia burgdorferi, Chlamydophila pneumoniae and Helicobacter pylori were measured by enzyme‐linked immunosorbent assay in 128 AD patients and 135 healthy controls. IB was defined as a composite serological measure of exposure to these common pathogens. Results: Seropositivities toward zero−two, three and four−five of these pathogens were found in 44%, 40% and 16% of healthy controls but in 20%, 44% and 36% of AD patients, respectively. IB, bacterial burden and viral burden were independently associated with AD after adjusting for age, gender, education, APOE genotype and various comorbidities. Mini‐Mental State Examination scores were negatively correlated with IB in all cases. Serum beta‐amyloid protein (Aβ) levels (i.e. Aβ40, Aβ42 and total Aβ) and inflammatory cytokines (i.e. interferon‐γ, tumor necrosis factor α, interleukin‐1β and interleukin‐6) in individuals exposed to four−five infectious pathogens were significantly higher than those exposed to zero−two or three pathogens. Conclusions: IB consisting of CMV, HSV‐1, B. burgdorferi, C. pneumoniae and H. pylori is associated with AD. This study supports the role of infection/inflammation in the etiopathogenesis of AD. Abstract : Clickhere to view the accompanying paper in this issue. Videocasts of this article are available in: English:http://player.polyv.net/videos/player.swf?vid=f6ee5715d9808c7a481b7ae727da00dd_f Mandarin:http://player.polyv.net/videos/f6ee5715d98ae743a9b0509d0900c91f_f.swf